2009
DOI: 10.1007/s00276-009-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

Current state of the art in perforator flap imaging with computed tomographic angiography

Abstract: Computed tomographic angiography (CTA) has become increasingly adopted for preoperative imaging in perforator flap surgery, as it has been shown to improve operative outcomes and decrease operating times prior to deep inferior epigastric artery perforator (DIEP) flap and anterolateral thigh perforator flap surgery. Current technologies are readily available for the preoperative imaging of all perforator flaps, however only sporadic reports of the use of CTA for the imaging of other perforators have been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 43 publications
3
29
0
2
Order By: Relevance
“…The efficacy and accuracy of CTA for mapping vasculature in other body regions has also been established. [6][7][8][9] An additional feature of the use of CTA in this case was the ability to clearly demonstrate not only vascular anatomy but also vascular communications with the soft-tissue structure being supplied. The iliac bone to be harvest was able to be mapped in three dimensions (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The efficacy and accuracy of CTA for mapping vasculature in other body regions has also been established. [6][7][8][9] An additional feature of the use of CTA in this case was the ability to clearly demonstrate not only vascular anatomy but also vascular communications with the soft-tissue structure being supplied. The iliac bone to be harvest was able to be mapped in three dimensions (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The use of CTA to evaluate the DCIA has only recently been described, 9,10 and such descriptions were limited to its cutaneous perforating branches, with the location and course of these perforators described for application in the DCIA osteo-cutaneous or osteo-musculo-cutaneous flap. In these studies, the size, path, and branches of the DCIA were demonstrated with a highdegree of accuracy able to visualize perforators as small as 0.3 mm in diameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aus diesem Grund hat beispielsweise die Gruppe um Yu [28] dieses Verfahren wieder verlassen und wendet stattdessen eine präoperative Markierung basierend auf Erkenntnissen aus anatomischen und klinischen Studien, genannt das ABC-System, an. Die CT-Angiographie bietet zwar eine detaillierte Darstellung der anatomischen Verhältnisse [17,19], ist jedoch unserer Meinung nach aufgrund der nicht unerheblichen Strahlenbelastung als kritisch zu werten. Die Farbduplexsonographie hingegen ist ein zuverlässiges Verfahren zur Perforatordarstellung beim ALT, deren Vorzüge von verschiedenen Autoren propagiert wurden [3,9,22].…”
Section: The Anterolateral Thigh Flap Its Versatility In Oncologicalunclassified